The Impact of Age on Outcomes in Chronic Obstructive Pulmonary Disease Differs by Relationship Status - Holm, Kristen E. (2013)
Alpha-1 antitrypsin deficiency (AATD) is a genetic condition that can lead to early-onset chronic obstructive pulmonary disease (COPD). The objective of this study was to examine the impact of age on psychological and clinical outcomes among individuals with AATD-associated COPD. 468 individuals with AATD-associated COPD (age 32 to 84 at baseline) completed questionnaires at baseline, 1- and 2-year follow-up. Age was examined as a predictor of depression, anxiety, health-related quality of life, and breathlessness at all three time points using linear mixed models. Age was associated with anxiety (b = −0.09, SE = 0.02, p < 0.001) and health-related quality of life (b = −0.29, SE = 0.09, p < 0.001). Age also had a statistically significant interaction with relationship status when predicting depression, health-related quality of life, and breathlessness. Among individuals who were single, younger age was associated with more symptoms of depression (b = −0.08, SE = 0.03, p < 0.01), worse health-related quality of life (b = −0.61, SE = 0.16, p < 0.001), and more breathlessness (b = −0.023, SE = 0.009, p < 0.01) throughout the two-year study. Age was not associated with these three outcomes among individuals who were married/part of an unmarried couple. Results suggest that individuals who develop a chronic illness at a young age, particularly those who are single, may be more likely to have worse psychological and clinical outcomes.